Nanostructures in suspended mono- and bilayer epitaxial graphene. (December 2017) - Chaste, Julien; Saadani, Amina; Jaffre, Alexandre; Madouri, Ali; Alvarez, José; Pierucci, Debora; Ben Aziza, Zeineb; Ouerghi, Abdelkarim
Abstract: Suspended graphene membrane presents a particular structure with fundamental interests and applications in nanomechanics, thermal transport and optoelectronics. Till now, the commonly used geometries are still quite simple and limited to the microscale. We propose here to overcome this problem by making nanostructures in suspended epitaxial bilayer graphene on a large scale and with a large variety of geometries. We also demonstrate a new hybrid thin film of SiC-graphene with an impressive robustness. Since the mechanics and thermal dissipation of a suspended graphene membrane are strongly related to its own geometry, we have in addition focused on thermal transport and strain engineering experiments. Micro-Raman spectroscopy mapping was successfully performed for various geometries with intrinsic properties measurements at the nanoscale. Our engineering of graphene geometry has permitted to reduce the thermal transport, release and modulate the strain in our structures. Graphical abstract: